Single coronary artery presenting dilated cardiomyopathy and hyperlipidemia with the SCN5A and APOA5 gene mutation: A case report and review of the literature - Hu, Xiaoxia; Kong, Jing; Niu, Tingting; Chen, Liang; Yang, Jingjing (Frontiers in Cardiovascular Medicine, 2023)
We present a 55-year-old man with chest tightness and dyspnea after activity lasting for 2 months diagnosed as single coronary artery (SCA) presenting dilated cardiomyopathy with the c.1858C>T mutation in the SCN5A gene. The computed tomography coronary angiogram (CTCA) showed congenital absence of the right coronary artery (RCA) and the right heart was nourished by the left coronary artery branch with no apparent stenosis. Transthoracic echocardiography (TTE) revealed enlargement of the left heart and cardiomyopathy. Cardiac magnetic resonance imaging (CMR) presented that dilated cardiomyopathy (DCM) was considered. Genetic testing displayed that c.1858C>T variant of the SCN5A gene could lead to Brugada syndrome and DCM. SCA is a rare congenital anomaly of the coronary anatomy and the case we reported as SCA accompanied with DCM is even rarer. We present a rare case of a 55-year-old man with dilated cardiomyopathy with the: c.1858C>T(p.Arg620Cys)/ c.1008G>A(p.(Pro336=) variant of the SCN5A gene, congenital absence of the right coronary artery, and the c.990_993delAACA(p.Asp332Valfs*5) variant of the APOA5 gene. To our knowledge, this is the first report of DCM combined with SCN5A gene mutation in SCA after searching Pubmed, CNKI and Wanfang databases. The most important finding is that we speculate that SCN5A gene variant maybe the cause of the absence of the right coronary artery present dilated cardiomyopathy in this patient.